Reconstruction of the ZnAl Mixed Oxides Into the Layered Double Hydroxide Catalysts Active in the Aldol Condensation of Furfural: The Role of ZnO Particles - Dubnová, Lada; Daňhel, Rostislav; Meinhardová, Vendula; Korolova, Valeriia; Smoláková, Lucie; Kondratowicz, Tomasz Stanisław; Kikhtyanin, Oleg; Čapek, Libor (FRONTIERS MEDIA SA, 2022)
A memory effect is the ability to restore the original, lamellar layered double hydroxide structure. Herein, we have described 1) the changes in the structural and basic properties of ZnAl mixed oxides during their transformation into ZnAl-reconstructed LDHs (RE-LDHs); 2) the extraordinary properties of ZnAl RE-LDHs compared to the original ZnAl LDHs; and 3) the changes of basic properties during the interaction of ZnAl RE-LDHs with atmospheric CO2. Aldol condensation was selected as probe reaction to prove the catalytic potential of ZnAl RE-LDHs. We have described a target method for preparing ZnAl RE-LDHs with a large number of basic sites. ZnAl RE-LDHs possess significantly higher furfural conversion in the aldol condensation of furfural than MOs. The structural, textural, and basic properties of the studied materials were described by temperature-programmed analysis, X-ray diffraction, N-2 adsorption, temperature-programmed desorption of CO2, and in-situ diffuse reflectance spectroscopy.
Přestavba ZnAl směsných oxidů do vrstevnatých dvouhydroxidových katalyzátorů aktivních v aldolové kondenzaci furfuralu: Role ZnO částic
Keywords: ZnAl reconstructed LDHs; temperature programmed techniques; in-situ DRS; structural properties; basic properties; Na leaching; aldol condensation of furfural; rekonstrukce; ZnAl LDH; teplotně programované techniky; strukturní vlastnosti; bazické vlastnosti; aldolová kondenzace